Evaluation Of Family Planning Program in Banjarsari Sub-District in 2017 - Joko Pramono, Damayanti Suhita, Affrice Damanik, (Solidaritas, 2018)
ABSTRACT The population control and Family Planning office of Surakarta City is the implementer of government regulation number 87 year 2014 about family planning program. The phenomenon of government regulation number 87 of 2014 in Surakarta City in terms of the implementation of Family Planning Program in field conducted by Family Planning Counselor is an important issue considering the regulation is made in the framework of population development and family development. Interest to examine the implementation of Family Planning program at the sub-district level implemented by the Banjarsari sub-district coordinator.The purpose of this study is to evaluate the implementation of public policies developed in the community by describing how government regulation number 87 of 2014 on population development, and family information system mentions.In this study, researchers used the theory of policy evaluation by William Dunn. There are six indicators that can be used in evaluating Dunns program policies, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness The research method that is deployed descriptive method with qualitative approach Therefore in informant selection is using a purposive method. Author also uses techniques such as, observation, interviews, and documentation for data collecting.The results of this study show the lack of socialization conducted by extension field family planning (PLKB) district Banjarsari in the implementation of family planning programs clearly and thoroughly then the limited human resources (SDM) so that socialization is not done thoroughly to the community and still lack of participation from local communities in playing an active role in participating in family planning programs. This study makes the researcher understand the difficulty of making a measure of public policy acceptable for the benefit of society. With the existence of government regulation concerning effort to arrange child birth, distance and ideal age of birth, regulate pregnancy, through the promotion, of protection and assistance in accordance with the reproductive rights to realize that quality family. Keyword : Program Evaluation, Family Planning